Socioeconomic inequalities in mental health in Australia: Explaining life shock exposure - Hashmi, Rubayyat; Alam, Khorshed; Gow, Jeff (My University, 2020)
Recent research suggests that there exists a strong link between life shocks and mental health. However, research on the distributional aspects of these shocks on mental health status is limited. In the health inequality literature no Australian studies have examined this relationship. This study examines the distributional impact of life shocks (negative life events and financial hardships) on mental health inequality among different socioeconomic groups in a longitudinal setting in Australia. This study analysed the data of 13,496 individuals from the Household, Income and Labour Dynamics in Australia (HILDA) survey, waves 12-17 (2012-2017). Using concentration index and Blinder-Oaxaca approaches, the study decomposed socioeconomic inequalities in mental health and changes in inequalities in mental health over the study period. The study used frailty indices to capture the severity of life shocks experienced by an individual. The results suggest that exposure to just one life shock will result in a greater risk of mental disorder in the most disadvantaged socioeconomic groups. The results also indicate that 24.7%-40.5% of pro-rich socioeconomic mental health inequality are due to life shocks. Financial hardship shocks contributes to 21.6%-35.4% of inequality compared with 2.3%-5.4% inequality generated by negative life event shocks across waves. Lower SES groups experience more life shocks than higher SES groups and in turn generate higher socioeconomic mental health inequality. Policies aimed at reducing socioeconomic inequality in mental health should account for these shocks when designing interventions.
Health Policy
Keywords: Disadvantage, adversity and resilience; Health and wellbeing